A20 takes on tumors: tumor suppression by an ubiquitin-editing enzyme - Malynn, Barbara A. (The Rockefeller University Press, 2009)
Many B cell cancers are characterized in part by the dysregulation of the NF-κB signaling pathway. A new study identifies somatic mutations in TNFAIP3, the gene encoding the NF-κB inhibitor A20, in Hodgkin lymphomas and primary mediastinal lymphomas. These data reveal the role of A20 as a tumor suppressor protein.